A Comparison of the Health Systems in China and India - Ma, Sai (RAND Corporation, 2008)
The health status of residents of China and India lags behind relative to other populations, and health gains in each country have been uneven across subpopulations. Each health system provides little protection against financial risk, and patient satisfaction is a lower priority than it should be. This paper compares the Chinese and Indian health systems to determine what approaches to improving health in these two countries do and do not work.